Exploring the Link: A Study of Secondary School English Language Teachers' Perceived and Actual Reading Skills Proficiency - Mengistie, Seyoum Tesfaye (Journal of Languages and Language Teaching, 2025)
Reading is the most important skills in language learning and teaching. This study aims at identifying secondary school English language teachers’ perceived and actual reading proficiency level and the correlation between these variables. The researchers employed mixed methods design and used questionnaire, proficiency test and interview to collect data from the participants. There were 112 secondary school teachers who take part in this study and among them four teachers were interviewed. The data gathered from the instruments were analyzed using SPSS version 24 for the quantitative and NVivo version 10 for the qualitative data. The results of this study revealed that secondary school English language teachers perceived proficiency level of reading skill was high. The proficiency test revealed that the levels secondary school English language teachers actual reading skills was medium. It was also found that there was a positive (r=.329) but not significant correlation between the teachers’ perceived and actual proficiency level of reading skills. The results indicated that teachers thought they had high proficiency level but their actual reading proficiency was not equivalent with their perceptions. This implies that there should be professional and skill development trainings given for the teachers. Besides, teachers should make themselves familiar with reading materials apart from the text book they are using in the classroom.